Using play to improve the social and emotional development of preschool children - San, Nang Mo Hline; Myint, Aye Aye; Oo, Cherry Zin (Southeast Asia Early Childhood Journal, 2021)
Every child deserves the opportunity to play during their preschool-age towards optimal development of physical, intellectual, social and emotional. However, parents or caregivers from the remote villages in Myanmar have not raised awareness of the play with their preschoolers. There was no preschool program in these remote villages in Myanmar. Therefore, this study aims to support parents and caregivers to nurture the social and emotional development of preschool children using play. This study shows them how they can create an environment for their preschoolers to improve the social and emotional development and the empirical evidence of the children development using play. Drawing on a pre-test-post-test control group design, a total of 90 preschool children involving 45 children in the experimental group and 45 children in the control group were observed before, during, and after the play program by using social and emotional development surveys. The descriptive and inferential data analysis results revealed that there was an effect of play program on preschool children’s social and emotional development. The program helps preschool children to optimize their social and emotional development. Implications of the results for the development and implementation of the play program are discussed.